ANALISIS PENGARUH RETURN ON ASSET (ROA), DEBT TO EQUITY RATIO (DER), DAN CASH RATIO (CR) TERHADAP DIVIDEN PAYOUT RATIO (DPR) PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (PERIODE 2015-2018) - I Made Suardana; Ida Ayu Putri Handayani; Erviva Fariantin (Akuntansi research UGR, 2020)
This study examines the effect of Return on Assets (ROA), Debt To Equity Ratio (DER), and Cash Ratio (CR) on Dividend Payout Ratio (DPR) on manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2018 period. So this research variable consists of 3 independent variables namely Return On Assets (X1), Debt To Equity Ratio (X2), and Cash Ratio (X3) and the dependent variable namely Dividend Payout Ratio (DPR) (Y). The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2015-2018 period of 163 companies. Samples were taken by using Purposive Sampling Technique to obtain a sample of 10 companies. with criteria based on companies for the period ending December 31, and companies that distribute dividends for 4 years in a row. The analysis technique used in this study is multiple linear regression and hypothesis testing using t-statistics to test the partial regression coefficient and f-statistics to test the feasibility of a research model with a level of significance of 0.05 / 5%. In addition, the classical assumption test was also performed which included the normality test, the multicollinearity test, the heteroscedasticity test and the autocorrelation test. The analysis shows that the Return On Asset (ROA) and Cash Ratio (CR) variables have positive and significant effects, while the Debt To Equity Ratio (DER) variable has a negative and significant effect on Dividend Payout Ratio (DPR).